ANALYZING THE SOCIAL VALUES CONTAINED IN THE FILM “TANAHSURGA KATANYA” BY DANIAL RIFKI - Maulida Fandani Amelia Putri; Imaniar Purbasari; Irfai Fathurohman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study examined the social values contained in the film Tanah Surga Katanya. Social values refer to community beliefs about what is considered good and useful in life and are reflected in daily behavior. The purpose of this study was to foster children’s social values through the film Tanah Surga Katanya. This research employed a qualitative method, with the film itself serving as the object of study. Data were collected through observation and documentation. The data were analyzed using content analysis, which involved data reduction, data presentation, and conclusion drawing to find, identify, process, and analyze the documents. The results showed that the film contained eight social values: (1) love for the homeland, (2) pride in the Indonesian nation, (3) mutual assistance, (4) mutual cooperation, (5) compassion, (6) dedication, (7) responsibility, and (8) care.